Involving Indonesia in the Philippine peace process : clearing away “inclement weather”? - Franco, Joseph Raymond S. (2012)
An Indonesian contingent has joined the Malaysian-led International Monitoring Team (IMT) overseeing the ceasefire in Mindanao between forces of the Philippines Government and the Moro Islamic Liberation Front. The deployment will arguably complement efforts to mediate between the two sides and address the socio-economic roots of the conflict.